AHP Approach To Developing a New Natural Toothpaste Product - Dikky Indrawan; Stevia Septiani; Galih Saputra Arista; Asep Rakhmat; Yessie W Sari; Nur A Nuzulia; Wulan T Wahyuni; Irmanida Batubara; Y. Aris Purwanto (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: A new approach to marketing an inventive product is needed as the development of a new natural toothpaste product is challenging. When choosing herbal-based products, consumers value taste and flavor, preferring natural, appealing flavors over synthetic flavors. Health advantages are also noteworthy, especially, herbal smells promote well-being and satisfaction.Purpose: The study main objective aimed to examine how the Analytic Hierarchy Process (AHP) was used to create a new natural toothpaste product. The study also aimed to design a strategy for innovative toothpaste commercialization based on nanohydroxyapatite (nanoHAP) and Curcuma aeruginosa.Design/methodology/approach: The AHP technique used to evaluate and prioritize elements of natural ingredient, and consumer preferences. The study framework identified herbal toothpaste benefits with known oral health benefits, such as antibacterial, anti-inflammatory, and desensitizing qualities, as well as consumer preferences for tooth paste. These attributes were ranked according to their performance using the AHP framework.Findings/Result: The results of the study stated that the new natural toothpaste, based on nanoHAP and Curcuma aeruginosa, was designed based on quality natural ingredients and consumer preference for naturalness, influencing formula design and marketing efforts. The strategy to develop new toothpaste aimed to provide a holistic health solution, emphasizing natural components and general health perspectives. This strategy could capture the attention of the target market and outpace competitors, attracting customers interested in natural health products.Conclusion: This study addresses the possibility of using nanoHAP alongside Curcuma aeruginosa in a natural toothpaste product that can enhance the remineralization and antibacterial characteristics of the dental product. The research suggests incorporating nanoHAP with Curcuma aeruginosa in a natural toothpaste product for holistic health solutions. Strategies include targeted marketing, loyalty programs, and strategic partnerships, ensuring a comprehensive and data-driven approach to reach and engage target audiences.Originality/value (State of the art): The AHP facilitates complete review, data-driven planning, and commercial viability for commercialization strategy. AHP aids in balancing functional benefits with quantifying subjective assessments, and incorporating customer feedback to increase product success in the competitive oral care industry. Keywords: nanohydroxyapatite (nanoHAP), curcuma aeruginosa, consumer preferences, functional benefits, commercialization strategy